Mouse Jagged1 Physically Interacts with Notch2 and Other Notch Receptors - Kiyoshí Shimizu; Shigeru Chiba; Keiki Kumano; Noriko Hosoya; Tokiharu Takahashi; Yoshinobu Kanda; Y. Hamada; Yoshio Yazaki; Hisamaru Hirai (1999)
The Delta/Serrate/LAG-2 (DSL) domain containing proteins are considered to be ligands for Notch receptors. However, the physical interaction between DSL proteins and Notch receptors is poorly understood. In this study, we cloned a cDNA for mouse Jagged1 (mJagged1). To identify the receptor interacting with mJagged1 and to gain insight into its binding characteristics, we established two experimental systems using fusion proteins comprising various extracellular parts of mJagged1, a "cell" binding assay and a "solid-phase" binding assay. mJagged1 physically bound to mouse Notch2 (mNotch2) on the cell surface and to a purified extracellular portion of mNotch2, respectively, in a Ca2+-dependent manner. Scatchard analysis of mJagged1 binding to BaF3 cells and to the soluble Notch2 protein demonstrated dissociation constants of 0.4 and 0.7 nm, respectively, and that the number of mJagged1-binding sites on BaF3 is 5,548 per cell. Furthermore, deletion mutant analyses showed that the DSL domain of mJagged1 is a minimal binding unit and is indispensable for binding to mNotch2. The epidermal growth factor-like repeats of mJagged1 modulate the affinity of the interaction, with the first and second repeats playing a major role. Finally, solid-phase binding assay showed that Jagged1 binds to Notch1 and Notch3 in addition to Notch2, suggesting that mJagged1 is a ligand for multiple Notch receptors.